Detection of bisphenol A using a novel surface plasmon resonance biosensor - Hegnerová, K; Piliarik, M; Šteinbachová, M; Flegelová, Z; Černohorská, H; Homola, J (Analytical and bioanalytical chemistry, 2010)
We present a compact surface plasmon resonance (SPR) biosensor for the detection of bisphenol A (BpA), an endocrine-disrupting chemical. The biosensor is based on an SPR sensor platform (SPRCD) and the binding inhibition detection format. The detection of BpA in PBS and wastewater was performed at concentrations ranging from 0.05 to 1,000 ng/ml. The limit of detection for BpA in PBS and wastewater was estimated to be 0.08 and 0.14 ng/ml, respectively. It was also demonstrated that the biosensor can be regenerated for repeated use. Results achieved with the SPR biosensor are compared with those obtained using ELISA and HPLC methods.
Keywords: fenoly; biosenzitivní techniky; Phenols; Surface Plasmon Resonance; Biosensing Techniques; Limit of Detection; limita detekce; povrchová plasmonová rezonance; Benzhydryl Compounds; chemické látky znečišťující vodu; Water Pollutants, Chemical; benzhydrylové sloučeniny